2-Chloro-3-hydroxymethyl-7,8-dimethylquinoline - Khan, F.N.; Roopan, S.M.; Hathwar, V.R.; Ng, S.W. (International Union of Crystallography, 2010)
All non-H atoms of the title compound, C(12)H(12)ClNO, are co-planar (r.m.s. deviation = 0.055 angstrom). The hydroxy H atom is disordered over two positions of equal occupancy. In the crystal, molecules are linked by O-H center dot center dot center dot O hydrogen bonds, generating zigzag chains running along the b axis.